Deskripsi Kemampuan Representasi Visual Materi Kelistrikan Berdasarkan Gender Peserta Didik Kelas IX SMP Negeri se-Kecamatan Panakkukang - Agung Erdiansah; Arie Arma Arsyad; Sitti Saenab (Celebes Science Education, 2025)
This study aims to determine the level of visual representation ability based on gender of students in class IX of State Junior High School in Panakkukang sub-district of Makassar City on static electricity and dynamic electricity material. The sample selected using the Slovin formula so that the sample in this study was 326 students who were randomly selected. The research instrument was in the form of a description question as many as 10 items. Based on the results of data analysis, it is known that the ability of visual representation based on gender of students in class IX of State Junior High School in Panakkukang sub-district of Makassar City on static electricity and dynamic electricity material, namely male and female students have an average value in the same category, namely moderate. The average value for male students is 42.80 with a medium category and female students have an average value of 42.52 with a medium category. Based on the ability category, female students are more dominant in the moderate to very high category, while men are more dominant in the low to high category.